Influence of sex in the match demands of elite beach football national teams - Reis, J.; Costa, J.; Prata, A.; Nascimento, L.; Brito, J. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Beach soccer is played by 5 players in a 35-37 m long and 26-28 m wide pitch covered with sand. It consists of three 12 minutes periods, with unlimited substitutions. It is characterized as an high intensity intermittent sport involving running, accelerations, jumps, and technical actions, hampered by the unstable surface (1). Current research does not provide information regarding the match demands of elite teams, especially in women (2). Therefore, we aimed to compare the match workload between male and female elite beach soccer players from national teams during official international competitions. METHODS: Thirteen matches from two national teams which were top-three finishers at the European Beach Soccer League 2022 were analyzed during the competition (Women: 7 matches, 10 players, 42 observations; Men: 6 matches, 11 players, 46 observations). Only field players participating in more than 25% of each match time were included in the analysis. Players used 10-Hz global positioning system units during all matches. External load variables included total distance covered (TD), high-speed distance (HSD, >13 and >10 km/h for men and women, respectively) number of sprints (>18 and >16 km/h) (2,3), number of accelerations and decelerations (> 2 m/s2; > -2 m/s2) and maximal Speed (MS). All variables were analyzed for absolute values and normalized to effective time played, expect MS. A mixed model analysis was used to compare the aforementioned variables between sexes. RESULTS: Men reached higher MS (22.5 ± 1.5 and 19.6 ± 1.5 km/h for men and women, respectively). On average, during the match, men completed significantly more HSD (350 ± 138 vs 172 ± 63 m); number of sprints (11.7 ± 8.8 vs 1.1 ± 1.1), sprint distance (102 ± 79.2 vs 8 ± 9.1 m) and number of accelerations and decelerations (83.2 ± 30.6 vs 39.4 ± 10.7, respectively) than women. There were no significant differences for TD between sex (2216 ± 648 vs 1890± 372 m). However, when normalizing for the effective time played (18.0 ± 6.1 vs 17.6 ± 3.7 min for men and women, respectively), men performed more TD (135 ± 29.9 and 112 ± 18.8 m/min), HSD (21.3 ± 8.1 and 10.9 ± 4.9 m/min), number of sprints (0.8 ± 0.8 and 0.6 ± 0.6 per min), accelerations and decelerations (5.0 ± 1.3 and 2.4 ± 0.8 per min). CONCLUSION: Our findings describe and compared the physical match demands of elite men beach soccer players with women, both in volume and intensity. Although both National teams can be considered as elite, these differences could be due to the fact that women`s beach soccer is less developed and amateur which can lead to fewer training opportunities and consequently less demanding physical match play.